In situ NMR and integrative proteomics reveal the interaction signature of serum α-synuclein - Jinfeng Huang; Rashik Ahmed; Madoka Akimoto; José Carlos Bozelli; Richard M. Epand; Giuseppe Melacini (Proceedings of the National Academy of Sciences, 2026)
Alpha-synuclein (αS) plays a central role in several neurodegenerative diseases. Although predominantly neuronal, αS is also present in peripheral fluids such as serum and cerebrospinal fluid (CSF), where it may contribute to disease propagation. However, its extracellular interactions remain poorly understood. By combining in situ NMR spectroscopy and bottom–up MS proteomics, we reveal that monomeric αS exhibits distinct interactomes in serum versus CSF. Both N- and C-terminal αS regions bind to serum components, while in CSF, αS remains largely unbound. The N- and C-terminal interactions are mechanistically diverse: C-terminal binding is electrostatic, whereas N-terminal interactions persist under high ionic strength, implicating hydrophobic interactions. Deletion of the first ten N-terminal residues, which include several hydrophobic side chains, abolishes these interactions, highlighting their functional importance. Proteomic profiling and NMR validation identify key αS serum partners, including albumin, γ-globulins, and lipoproteins, which, together, are sufficient to recapitulate the serum αS interactome and elicit redundant interactions with the αS N-terminal region. Despite such redundancy, αS methionine oxidation selectively disrupts N-terminal binding, suggesting a redox-sensitive mechanism regulating the αS extracellular interactome. Notably, C-terminal interactions are preserved when the N-terminal binding is detuned, indicating that the N- and C-termini elicit independent interactions with the extracellular matrix, a marked difference from the intracellular milieu. These findings uncover dynamic and fluid-specific αS interaction signatures, offering new molecular insights into its peripheral roles and identifying potential new epitopes as synucleinopathy biomarkers. These results are also relevant for other amyloidogenic intrinsically disordered proteins (IDPs), for which αS serves as a prototype.